Some of Imam IbnHajar al-Haytami's fatwas (d.: 974 AH) in the Chapter of the Gift : A Comparative Study (Islamic Sciences Journal, 2024)
When looking at the scientific biography of Imam al-Haythami (d.: 974 AH) (may Allah have mercy on him), we find a vastness in his sciences, diversity, and differences, so we stand on his books on interpretation, readings, Arabic Language, jurisprudence, and so on. The book of the major jurisprudential fatwas is the subject of our research.       It included in its folds his fatwas which are collected by one of his students, except that we tried through this research  to shed light on some of these fatwas - the chapter on gift in particular - and to study them in a comparative study to clarify the jurisprudence of Imam Al-Haythami, and mastering (may Allah have mercy on him)  the arts of this science, like other sciences in which he excelled.
Keywords: Hetami, gift, commons, benefits, return.